Environment-friendly plate with self-purification function and preparation method thereof
By combining MOFs and nitrogen-doped carbon-based photocatalysts in environmentally friendly plates, the problems of saturation of physical adsorption materials and ultraviolet light dependence of photocatalytic materials in the prior art are solved, and efficient adsorption and degradation of harmful gases under visible light conditions are achieved, thereby enhancing the efficiency of adsorption and degradation of harmful gases. The self-purification and multiple properties of the material.
Patent Information
- Application Number
- CN202411685861.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, physical adsorbent materials can only temporarily capture harmful gases, are easily saturated and cannot completely decompose harmful substances, while photocatalytic materials need to be effectively degraded under ultraviolet light conditions.
Using environmentally friendly plates containing MOFs, nitrogen-doped carbon-based photocatalysts, graphene oxides, self-healing polymers, antibacterial agents, humidity-regulating materials, ultraviolet absorbers, tougheners, binders and thickeners, through MOFs The harmful gases are adsorbed at high specific surface area and photocatalytic degradation is carried out by a nitrogen-doped carbon-based photocatalyst under visible light conditions.
It realizes efficient adsorption and degradation of harmful gases under visible light conditions, enhances the self-purification ability of the material, and has multiple properties such as self-healing, antibacterial, humidity adjustment and toughening, which is suitable for improving indoor air quality.
Smart Images

Figure CN119410161A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building decoration materials, in particular to an environmentally friendly plate with self-purification capability and a preparation method thereof. Background Art
[0002] With the widespread use of modern building decoration materials, indoor air pollution is becoming increasingly serious, especially the release of harmful volatile organic compounds such as free formaldehyde and benzene, which poses a threat to human health. Formaldehyde and benzene are highly volatile and toxic. Long-term exposure can cause respiratory diseases, allergic reactions, and may even cause cancer. Therefore, how to effectively remove these harmful gases and improve indoor air quality has become a technical problem that needs to be solved in the field of building materials.
[0003] At present, the commonly used air purification technologies on the market mainly include two categories: physical adsorption and chemical decomposition. The physical adsorption method mainly adsorbs harmful gases through porous materials such as activated carbon, but physical adsorption can only temporarily capture pollutants, is easily saturated and cannot completely decompose harmful gases. The chemical decomposition method decomposes harmful gases into harmless small molecules such as carbon dioxide and water through means such as photocatalysis, thereby achieving complete purification. However, existing photocatalytic materials such as titanium dioxide can usually only show good catalytic effects under ultraviolet light conditions, while indoor lighting is mainly visible light, which greatly limits the effect of photocatalytic materials in practical applications. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides an environmentally friendly plate with self-purification capabilities and a preparation method thereof, which solves the problems in the prior art that physical adsorption materials can only temporarily capture harmful gases, are easily saturated and cannot completely decompose harmful substances, and photocatalytic materials can only effectively degrade harmful gases under ultraviolet light conditions.
[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: an environmentally friendly plate with self-purification ability, comprising the following components by weight percentage: 30-40% MOFs, 15-25% nitrogen-doped carbon-based photocatalyst, 5-10% graphene oxide, 5-10% self-healing polymer, 0.5-2% antibacterial agent, 3-8% humidity regulating material, 1-3% ultraviolet absorber, 1-3% toughening agent, 5-10% binder and 0.5-1% thickener.
[0006] Preferably, the self-healing polymer is selected from one of polyurea, polyurethane, polyisobutylene or polysiloxane, the antibacterial agent is selected from one of silver ions, zinc oxide, copper-based antibacterial materials or titanium dioxide, and the humidity regulating material is selected from one of diatomaceous earth, montmorillonite, sepiolite, activated carbon or zeolite.
[0007] Preferably, the ultraviolet absorber is optionally selected from one of silica-coated titanium dioxide, hydroxyphenylbenzotriazole compounds, zinc oxide, benzophenone compounds or nano cerium oxide, the toughening agent is optionally selected from one of polyvinyl alcohol, nitrile rubber powder, polyacrylate, epoxy resin modifier or silicone rubber, the binder is optionally selected from one of water-based polyurethane, sodium silicate solution, epoxy resin, polyvinyl formal or acrylic emulsion, and the thickener is optionally selected from one of hydroxypropyl methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, xanthan gum or bentonite.
[0008] A method for preparing an environmentally friendly plate with self-purification capability is prepared by using the component materials contained in the environmentally friendly plate with self-purification capability described above, and comprises the following steps:
[0009] Synthesis of MOFs;
[0010] Preparation and compounding of nitrogen-doped carbon-based photocatalysts;
[0011] Composite of graphene oxide;
[0012] the introduction of antimicrobial agents and humidity regulating materials;
[0013] The ultraviolet light absorber is added into the mixture and stirred;
[0014] Introduction of toughening agents and self-healing polymers;
[0015] Addition and Forming of Binders and Thickeners
[0016] Preferably, the MOFs synthesis step specifically includes the following steps:
[0017] The metal precursor and the organic ligand were mixed in a molar ratio of 1:1;
[0018] Dissolving the mixture in N,N-dimethylformamide solvent with a solvent concentration of 0.1-0.2 mol / L;
[0019] Solvothermal reaction is carried out at a temperature of 120-150°C and the reaction time is 12-24h;
[0020] After the reaction was completed, the product was washed three times with ethanol;
[0021] The washed product was placed in a vacuum oven at 80-100°C and dried for 8-12 hours.
[0022] Preferably, the preparation and compounding steps of the nitrogen-doped carbon-based photocatalyst specifically include the following steps:
[0023] Urea or melamine is placed in a closed crucible as a nitrogen source and calcined at 500-600° C. for 2-4 hours to prepare nitrogen-doped carbonized graphite;
[0024] Mix tetrabutyl titanate, ethanol and urea, and adjust the pH of the solution to 3-4;
[0025] Stir at 50-60°C for 4-6 hours to form a gel;
[0026] The gel was dried at 70-80℃ for 10-12h and then calcined at 400-500℃ for 2-3h to obtain nitrogen-doped TiO 2 Nanoparticles;
[0027] MOFs and nitrogen-doped photocatalysts were mixed in a mass ratio of 2:1, dispersed in ethanol and subjected to ultrasonic treatment for 30-60 min;
[0028] The mixture was stirred at room temperature for 6-12 h and then dried at 70-80 °C to remove the solvent.
[0029] Preferably, the graphene oxide compounding step specifically includes the following steps:
[0030] Dispersing graphene oxide in deionized water at a concentration of 0.05-0.1 mg / mL, and performing ultrasonic dispersion for 25-30 min;
[0031] Slowly add the MOFs-photocatalyst composite powder into the graphene oxide suspension and stir for 3-4 hours;
[0032] The mixture is dried at 70-80°C to form a stable composite powder.
[0033] Preferably, in the step of introducing the antimicrobial agent and the humidity regulating material, the antimicrobial agent and the humidity regulating material are weighed according to weight percentage and added to the composite powder, and stirred for 2-3 hours.
[0034] Preferably, the step of introducing the toughening agent and the self-healing polymer specifically comprises the following steps:
[0035] The toughening agent is made into a solution with a concentration of 5-10wt%;
[0036] Slowly add the composite powder into the toughening agent solution and stir for 3-6 hours;
[0037] Dissolving the self-healing polymer in a suitable solvent at a concentration of 10-20wt%;
[0038] The toughened composite material is added into the self-healing polymer solution and stirred until uniform.
[0039] Preferably, the steps of adding and molding the binder and thickener specifically include the following steps:
[0040] The binder and the thickener are weighed and added to the composite material according to weight percentage respectively, and the mixture is fully stirred;
[0041] Use molding or spraying process to evenly apply the mixed material on the surface of the building substrate;
[0042] The coated material is placed under ultraviolet light or in an environment of 80-100°C for curing for 2-4 hours to complete the cross-linking and curing of the material.
[0043] The present invention provides an environmentally friendly plate with self-purification capability and a preparation method thereof. The plate has the following beneficial effects:
[0044] 1. The present invention adopts MOFs as the main adsorption material. Through its high specific surface area and porosity, it can effectively adsorb harmful gases such as free formaldehyde and benzene in the air. At the same time, the introduction of nitrogen-doped carbon-based photocatalyst produces a photocatalytic reaction under visible light conditions, decomposing these organic pollutants into harmless carbon dioxide and water, thereby realizing the self-purification function of the material.
[0045] 2. The self-healing polymer of the present invention gives the material the ability to self-repair when physically damaged, ensuring the long-term durability of the material and avoiding the degradation of material performance due to minor damage, thereby extending the service life of the material.
[0046] 3. The present invention effectively inhibits the growth of bacteria and microorganisms by adding antibacterial agents to the material, ensuring the hygienic performance of the material during use. At the same time, the addition of humidity regulating materials enables the material to remain stable in different humidity environments, thereby adapting to various building environment requirements.
[0047] 4. The ultraviolet absorber of the present invention can effectively absorb ultraviolet rays and protect the material from degradation caused by ultraviolet radiation, thereby maintaining the physical stability and long-term self-purification effect of the material, and is suitable for indoor and outdoor application environments with strong sunlight. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION
[0049] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Please see attached Figure 1The embodiment of the present invention provides an environmentally friendly plate with self-purification ability, which includes the following components by weight percentage: 30-40% MOFs, 15-25% nitrogen-doped carbon-based photocatalyst, 5-10% graphene oxide, 5-10% self-healing polymer, 0.5-2% antibacterial agent, 3-8% humidity regulating material, 1-3% ultraviolet absorber, 1-3% toughening agent, 5-10% binder and 0.5-1% thickener.
[0051] The self-repairing polymer is selected from one of polyurea, polyurethane, polyisobutylene or polysiloxane, the antibacterial agent is selected from one of silver ions, zinc oxide, copper-based antibacterial materials or titanium dioxide, and the humidity regulating material is selected from one of diatomaceous earth, montmorillonite, sepiolite, activated carbon or zeolite.
[0052] The ultraviolet absorber is optionally selected from one of silica-coated titanium dioxide, hydroxyphenylbenzotriazole compounds, zinc oxide, benzophenone compounds or nano cerium oxide; the toughening agent is optionally selected from one of polyvinyl alcohol, nitrile rubber powder, polyacrylate, epoxy resin modifier or silicone rubber; the binder is optionally selected from one of waterborne polyurethane, sodium silicate solution, epoxy resin, polyvinyl formal or acrylic emulsion; the thickener is optionally selected from one of hydroxypropyl methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, xanthan gum or bentonite.
[0053] A method for preparing an environmentally friendly plate with self-purification capability is prepared by using the component materials contained in the environmentally friendly plate with self-purification capability, and comprises the following steps:
[0054] Synthesis of MOFs;
[0055] Preparation and compounding of nitrogen-doped carbon-based photocatalysts;
[0056] Composite of graphene oxide;
[0057] the introduction of antimicrobial agents and humidity regulating materials;
[0058] The ultraviolet light absorber is added into the mixture and stirred;
[0059] Introduction of toughening agents and self-healing polymers;
[0060] Addition and molding of binders and thickeners.
[0061] The synthesis steps of MOFs specifically include the following steps:
[0062] The metal precursor and the organic ligand were mixed in a molar ratio of 1:1;
[0063] The mixture is dissolved in N,N-dimethylformamide solvent with a solvent concentration of 0.1-0.2 mol / L;
[0064] Solvothermal reaction is carried out at a temperature of 120-150°C and the reaction time is 12-24h;
[0065] After the reaction was completed, the product was washed three times with ethanol;
[0066] The washed product was placed in a vacuum oven at 80-100°C and dried for 8-12 hours.
[0067] The preparation and compounding steps of the nitrogen-doped carbon-based photocatalyst specifically include the following steps:
[0068] Urea or melamine is placed in a closed crucible as a nitrogen source and calcined at 500-600° C. for 2-4 hours to prepare nitrogen-doped carbonized graphite;
[0069] Mix tetrabutyl titanate, ethanol and urea, and adjust the pH of the solution to 3-4;
[0070] Stir at 50-60°C for 4-6 hours to form a gel;
[0071] The gel was dried at 70-80℃ for 10-12h and then calcined at 400-500℃ for 2-3h to obtain nitrogen-doped TiO 2 Nanoparticles;
[0072] MOFs and nitrogen-doped photocatalysts were mixed in a mass ratio of 2:1, dispersed in ethanol and subjected to ultrasonic treatment for 30-60 min;
[0073] The mixture was stirred at room temperature for 6-12 h and then dried at 70-80 °C to remove the solvent.
[0074] The composite step of graphene oxide specifically includes the following steps:
[0075] Dispersing graphene oxide in deionized water at a concentration of 0.05-0.1 mg / mL, and performing ultrasonic dispersion for 25-30 min;
[0076] Slowly add the MOFs-photocatalyst composite powder into the graphene oxide suspension and stir for 3-4 hours;
[0077] The mixture is dried at 70-80°C to form a stable composite powder.
[0078] In the step of introducing the antimicrobial agent and the humidity regulating material, the antimicrobial agent and the humidity regulating material are weighed according to the weight percentage and added to the composite powder, and stirred for 2-3h.
[0079] The steps of introducing the toughening agent and the self-healing polymer specifically include the following steps:
[0080] The toughening agent is made into a solution with a concentration of 5-10wt%;
[0081] Slowly add the composite powder into the toughening agent solution and stir for 3-6 hours;
[0082] Dissolving the self-healing polymer in a suitable solvent at a concentration of 10-20wt%;
[0083] The toughened composite material is added into the self-healing polymer solution and stirred until uniform.
[0084] The steps of adding and molding the binder and thickener specifically include the following steps:
[0085] The binder and the thickener are weighed and added to the composite material according to weight percentage respectively, and the mixture is fully stirred;
[0086] Use molding or spraying process to evenly apply the mixed material on the surface of the building substrate;
[0087] The coated material is placed under ultraviolet light or in an environment of 80-100°C for curing for 2-4 hours to complete the cross-linking and curing of the material.
[0088] Embodiment 1
[0089] Synthesis of MOFs:
[0090] The metal precursor ZrCl 4 Mix with terephthalic acid in a 1:1 molar ratio.
[0091] The mixture was dissolved in 0.1 mol / L N,N-dimethylformamide.
[0092] The solvothermal reaction was carried out at 120 °C for 12 h.
[0093] After the reaction was completed, the product was washed three times with ethanol.
[0094] The washed product was placed in a vacuum oven at 80°C and dried for 8 hours.
[0095] Preparation and composite of nitrogen-doped carbon-based photocatalysts:
[0096] Urea was used as a nitrogen source and calcined at 500 °C for 2 h to generate nitrogen-doped carbonized graphite.
[0097] Tetrabutyl titanate, ethanol and urea were mixed and the pH of the solution was adjusted to 3.
[0098] The mixture was stirred at 50°C for 4 hours to form a gel.
[0099] The gel was dried at 70 °C for 10 h and then calcined at 400 °C for 2 h to obtain nitrogen-doped TiO 2 Nanoparticles.
[0100] MOFs and nitrogen-doped photocatalysts were mixed in a mass ratio of 2:1, dispersed in ethanol, ultrasonically treated for 30 min, stirred at room temperature for 6 h, and dried at 70 °C to remove the solvent.
[0101] Graphene oxide compound:
[0102] Graphene oxide was dispersed in deionized water at a concentration of 0.05 mg / mL and ultrasonically dispersed for 25 minutes.
[0103] The MOFs-photocatalyst composite powder was added into the graphene oxide suspension and stirred for 3 hours.
[0104] The mixture was dried at 70°C to form a stable composite powder.
[0105] Introduction of antimicrobial agents and humidity regulating materials:
[0106] Add 0.5% zinc oxide and 3% diatomaceous earth and stir for 2 hours.
[0107] Addition of UV absorbers:
[0108] Add 1% SiO 2 Coated TiO 2 As a UV absorber, stir well.
[0109] Introduction of toughening agents and self-healing polymers:
[0110] A 5 wt % polyvinyl alcohol toughening agent solution was used, added to the composite powder, and stirred for 3 hours.
[0111] Use 10wt% of polyurea self-repairing polymer solution, add it into the toughened composite material, and stir it evenly.
[0112] Addition and molding of binders and thickeners:
[0113] Add 5% water-based polyurethane and 0.5% carboxymethyl cellulose and stir well.
[0114] Cure with UV light for 2 hours.
[0115] Embodiment 2
[0116] Synthesis of MOFs:
[0117] The solvent concentration was increased to 0.15 mol / L, the reaction temperature was raised to 130°C, and the reaction time was extended to 16 hours.
[0118] The drying temperature was increased to 90°C for 10 hours.
[0119] Preparation and composite of nitrogen-doped carbon-based photocatalysts:
[0120] The nitrogen source was replaced with melamine, and the calcination temperature was increased to 550°C for 3 hours.
[0121] The reaction temperature was raised to 55°C and stirred for 5 hours.
[0122] The drying temperature was increased to 75°C and the drying time was 11 hours. The calcination temperature was 450°C and the time was 2.5 hours.
[0123] The ultrasonic treatment time was extended to 45 min and the stirring time was increased to 8 h.
[0124] Graphene oxide compound:
[0125] The graphene oxide concentration was increased to 0.075 mg / mL and ultrasonic dispersion was performed for 28 minutes.
[0126] The stirring time was increased to 3.5 hours.
[0127] Introduction of antimicrobial agents and humidity regulating materials:
[0128] Silver ions were used as the antibacterial agent and montmorillonite was used as the humidity regulating material, and the mixture was stirred for 2.5 hours.
[0129] Addition of UV absorbers:
[0130] The amount of UV absorber added was increased to 2%.
[0131] Introduction of toughening agents and self-healing polymers:
[0132] The toughening agent concentration was increased to 7 wt % and stirred for 4 hours.
[0133] The self-healing polymer was replaced with polyurethane at a concentration of 15wt%.
[0134] Addition and molding of binders and thickeners:
[0135] The thickener was replaced with xanthan gum.
[0136] The curing temperature is 80°C and the curing time is extended to 3 hours.
[0137] Embodiment 3
[0138] Synthesis of MOFs:
[0139] The solvent concentration was increased to 0.2 mol / L, the reaction temperature was 140°C, the reaction time was 18 hours, and the drying temperature was increased to 95°C, the time was 11 hours.
[0140] Preparation and composite of nitrogen-doped carbon-based photocatalysts:
[0141] The nitrogen source is a mixture of urea and melamine, the calcination temperature is 600°C, the time is 3.5 hours. The reaction temperature is raised to 60°C and stirred for 6 hours.
[0142] The ultrasonic treatment time was 60 minutes and the stirring time was 10 hours.
[0143] Graphene oxide compound:
[0144] Graphene oxide concentration 0.1 mg / mL, ultrasonic dispersion for 30 minutes, stirring time 4 hours. Introduction of antibacterial agent and humidity regulating material:
[0145] The antibacterial agent is a copper-based material, and the humidity regulating material is sepiolite, and stirred for 3 hours. Addition of UV absorber:
[0146] The amount of UV absorber added is 3%.
[0147] Introduction of toughening agents and self-healing polymers:
[0148] The toughening agent concentration was 10 wt%, and the mixture was stirred for 6 hours.
[0149] The self-healing polymer was replaced with polyisobutylene at a concentration of 20wt%.
[0150] Addition and molding of binders and thickeners:
[0151] The binder is sodium silicate solution, the curing temperature is 90°C, and the curing time is 3.5 hours.
[0152] Embodiment 4
[0153] Synthesis of MOFs:
[0154] The reaction temperature was 145°C and the reaction time was 20 hours.
[0155] The drying temperature is 100°C and the drying time is 12 hours.
[0156] Preparation and composite of nitrogen-doped carbon-based photocatalysts:
[0157] Using carbon and nitrogen co-doped TiO 2 , maintain the calcination temperature at 450°C.
[0158] Ultrasonic treatment was performed for 60 minutes and stirring time was 12 hours.
[0159] Graphene oxide compound:
[0160] The ultrasonic dispersion time was 30 minutes and the stirring time was 4.5 hours.
[0161] Introduction of antimicrobial agents and humidity regulating materials:
[0162] The antimicrobial agent is copper-based and the humidity regulating material is replaced with activated carbon.
[0163] Addition of UV absorbers:
[0164] The UV absorber uses hydroxyphenylbenzotriazole compounds, with an addition amount of 3%. Introduction of toughening agents and self-healing polymers:
[0165] Polyacrylate was used as the toughening agent and the mixture was stirred for 6 hours.
[0166] Addition and molding of binders and thickeners:
[0167] The thickener is bentonite, the curing temperature is 100°C, and the curing time is 3.5 hours.
[0168] Embodiment 5
[0169] Synthesis of MOFs:
[0170] The reaction temperature was 145°C and the reaction time was 24 hours.
[0171] Preparation and composite of nitrogen-doped carbon-based photocatalysts:
[0172] Select nitrogen-doped TiO 2 , ultrasonic treatment for 60 minutes and stirring time for 12 hours.
[0173] Graphene oxide compound:
[0174] Dispersion concentration was 0.1 mg / mL, ultrasonication was performed for 30 minutes, and stirring was performed for 4.5 hours.
[0175] Introduction of antimicrobial agents and humidity regulating materials:
[0176] The antibacterial agent and humidity regulating material remain unchanged and stirred for 3.5 hours.
[0177] Addition of UV absorbers:
[0178] The amount of UV absorber added is 3%.
[0179] Introduction of toughening agents and self-healing polymers:
[0180] The toughening agent and self-healing polymer remain unchanged, and the stirring time is kept at the maximum value.
[0181] Addition and molding of binders and thickeners:
[0182] The curing time is extended to 4 hours.
[0183] Summary: The above five embodiments are based on the same core components and preparation steps, and gradually optimize various process parameters, including reaction temperature, time, concentration, etc., to improve the self-purification, stability and service life of the material. The adjustment of each embodiment increases innovation on the basis of the previous embodiment to ensure that the material can adapt to different architectural decoration environment requirements.
[0184] Experimental design
[0185] 1. Purpose of the experiment
[0186] 1. Adsorption capacity test: verify the performance of the material of the present invention in the adsorption of formaldehyde and benzene, and compare it with existing activated carbon and zeolite materials to prove the advantage of the material of the present invention in adsorption effect.
[0187] 2. Photocatalytic performance test: Through comparative tests under ultraviolet light and visible light conditions, the performance of the material of the present invention in photocatalytic degradation of formaldehyde and benzene was evaluated, and compared with the traditional TiO 2 Photocatalysts for comparison.
[0188] 3. Antibacterial performance test: verify the antibacterial effect of the material of the present invention on Staphylococcus aureus and Escherichia coli, evaluate its antibacterial durability, and compare it with traditional silver-based antibacterial materials.
[0189] 4. Humidity regulation performance test: The moisture absorption and release capacity of the material of the present invention under different humidity conditions was tested and compared with the zeolite material to verify its humidity regulation performance.
[0190] 5. Durability and self-healing test: Evaluate the durability and self-healing ability of the material through accelerated aging and mechanical damage tests.
[0191] 2. Experimental Materials
[0192] Control group:
[0193] Activated carbon materials: used to adsorb VOCs such as formaldehyde and benzene, but lack photocatalytic and antibacterial properties.
[0194] Pure TiO 2 Photocatalysts: Used to decompose VOCs, but only perform well under UV light and have no adsorption or antibacterial properties.
[0195] Silver-based antibacterial coating materials: commonly used to inhibit bacterial growth, but lack adsorption and photocatalytic capabilities.
[0196] Zeolite: used for humidity regulation and adsorption, but has no photocatalytic and antibacterial properties.
[0197] Experimental group: material samples of Examples 1 to 5.
[0198] Experiment 1: Adsorption capacity test of formaldehyde and benzene
[0199] Purpose:
[0200] The performance of the material of the present invention in the adsorption of formaldehyde and benzene was verified and compared with existing activated carbon and zeolite materials to prove the advantage of the material of the present invention in the adsorption effect.
[0201] Experimental steps:
[0202] The initial concentration was 1 mg / mL. 3 A mixture of formaldehyde and benzene was filled into 1m 3 Sealed test box.
[0203] The control group materials (activated carbon, zeolite) and the samples of Examples 1 to 5 of the present invention were placed in the experimental box respectively, and the weight of each material was 5 g.
[0204] Gas samples were collected every 2 hours and the concentrations of formaldehyde and benzene were measured using gas chromatography-mass spectrometry (GC-MS) for 24 hours.
[0205] Calculate the adsorption rate of each material and draw a curve of adsorption rate changing with time.
[0206] Experimental data recording form:
[0207] Table 1.1 Formaldehyde adsorption rate data table:
[0208]
[0209] Table 1.2 Benzene adsorption rate data table:
[0210]
[0211] Experimental summary:
[0212] The experimental data show that the material of the present invention is significantly superior to traditional adsorption materials (activated carbon, zeolite) in the adsorption of formaldehyde and benzene. In particular, the adsorption efficiency of Example 5 for formaldehyde and benzene within 24 hours reached 82% and 80%, respectively, which is significantly higher than 55% and 48% of activated carbon. This verifies the advantages of the material of the present invention in the adsorption of harmful gases and proves that it is suitable for high-efficiency air purification.
[0213] Experiment 2: Photocatalytic degradation efficiency test (under visible light and ultraviolet light conditions)
[0214] Purpose:
[0215] The performance of the material of the present invention in photocatalytic degradation of formaldehyde and benzene was evaluated by comparative tests under ultraviolet and visible light conditions, and compared with the traditional TiO 2 Photocatalysts for comparison.
[0216] Experimental steps:
[0217] Prepare 1 mg / m in a closed reaction device 3 A mixture of formaldehyde and benzene.
[0218] TiO 2 The materials and samples of Examples 1 to 5 of the present invention were placed in a reaction device respectively, and the mass of the samples was 5 g.
[0219] First test under ultraviolet light for 8 hours, and record the concentrations of formaldehyde and benzene in the gas every hour.
[0220] Change the light source to visible light, continue the test for 8 hours, and record the formaldehyde and benzene concentrations in the gas.
[0221] Calculate the degradation rate.
[0222] Experimental data recording form:
[0223] Table 2.1 Formaldehyde degradation rate data under ultraviolet light:
[0224]
[0225] Table 2.2 Formaldehyde degradation rate data under visible light
[0226]
[0227] Experimental summary:
[0228] Under ultraviolet and visible light conditions, the photocatalytic degradation efficiency of the material of the present invention is significantly better than that of traditional TiO 2 The formaldehyde degradation rate of the material, especially the fifth embodiment, under visible light conditions reached 85%, which is higher than that of TiO 2 The 35% of the material is 50 percentage points higher. This verifies the innovation and practicality of the material of the present invention in photocatalysis.
[0229] Experiment 3: Antibacterial performance test
[0230] Purpose:
[0231] The antibacterial effect of the material of the present invention on Staphylococcus aureus and Escherichia coli was verified, and its antibacterial persistence was evaluated and compared with traditional silver-based antibacterial materials.
[0232] Experimental procedures
[0233] Staphylococcus aureus and Escherichia coli were diluted to 1 × 10 6 CFU / mL.
[0234] The silver-based antibacterial material and the samples of Examples 1 to 5 of the present invention were placed in a sterile culture dish.
[0235] The bacterial solution was evenly spread on the surface of the material and cultured at 37°C for 24 hours.
[0236] Samples were taken every 6 hours and the number of colonies was determined.
[0237] Calculate the inhibition rate.
[0238] Experimental data recording form:
[0239] Table 3.1 Staphylococcus aureus antibacterial rate data table:
[0240]
[0241] Table 3.2 Escherichia coli antibacterial rate data table:
[0242]
[0243] Experimental summary:
[0244] The experimental results show that the antibacterial performance of the material of the present invention is superior to that of the traditional silver-based antibacterial material, especially the antibacterial rates of Example 5 against Staphylococcus aureus and Escherichia coli reach 95% and 97% respectively within 24 hours, showing excellent antibacterial persistence.
[0245] Experiment 4: Humidity Regulation Performance Test
[0246] Purpose:
[0247] The moisture absorption and release capabilities of the material of the present invention under different humidity conditions were tested and compared with the zeolite material to verify its humidity regulating performance.
[0248] Experimental steps:
[0249] The samples of Examples 1 to 5 and the zeolite material were placed in a sealed box.
[0250] The RH was gradually increased from 20% to 80% and the moisture absorption of the material was recorded.
[0251] The humidity was then reduced to 20% RH and the moisture release rate was recorded.
[0252] The weight change was recorded every 2 hours and the test continued for 48 hours.
[0253] Table 4:
[0254]
[0255] Experimental summary:
[0256] Experimental data show that the material of the present invention has better performance in humidity regulation than traditional zeolite materials, especially Example 5, whose moisture absorption within 48 hours reaches 2.2 g / g, showing excellent humidity regulation ability.
[0257] Experiment 5: Durability and self-repair ability test
[0258] Purpose:
[0259] The durability and self-repairing ability of the materials of the present invention after aging and mechanical damage were evaluated and compared with traditional building materials.
[0260] Experimental steps:
[0261] The samples of Examples 1 to 5 and traditional building materials were placed in an accelerated aging chamber at 80° C. and 80% RH and tested for 7 days.
[0262] The physical form changes of the material were measured every 24 hours, and the changes in the adsorption and degradation properties were recorded.
[0263] Scratch the surface of the material after aging and observe the self-healing effect.
[0264] Table 5:
[0265]
[0266] Experimental summary:
[0267] The material of the present invention performs excellently in terms of durability and self-repairing ability, especially Example 5 can still retain 92% of the degradation performance after 7 days of accelerated aging, and the scratch self-repairing effect is remarkable.
[0268] Summary:
[0269] Based on the above experiments, the material of the present invention is significantly superior to the traditional material in terms of adsorption capacity, photocatalytic degradation efficiency, antibacterial performance, humidity regulation ability and durability. Each performance test shows that the material of the present invention is suitable for high-efficiency air purification and has a wide range of practical application value.
[0270] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Environmentally friendly board with self-purification ability, characterized by: The invention comprises the following components by weight percentage: 30-40% of MOFs, 15-25% of nitrogen-doped carbon-based photocatalyst, 5-10% of graphene oxide, 5-10% of self-healing polymer, 0.5-2% of antibacterial agent, 3-8% of humidity regulating material, 1-3% of ultraviolet absorber, 1-3% of toughening agent, 5-10% of binder and 0.5-1% of thickener.
2. The environmentally friendly plate with self-purification ability according to claim 1, characterized in that: The self-healing polymer is selected from one of polyurea, polyurethane, polyisobutylene or polysiloxane, the antibacterial agent is selected from one of silver ions, zinc oxide, copper-based antibacterial materials or titanium dioxide, and the humidity regulating material is selected from one of diatomaceous earth, montmorillonite, sepiolite, activated carbon or zeolite.
3. The environmentally friendly plate with self-purification capability according to claim 1, characterized in that: The ultraviolet absorber is optionally selected from one of silica-coated titanium dioxide, hydroxyphenylbenzotriazole compounds, zinc oxide, benzophenone compounds or nano cerium oxide; the toughening agent is optionally selected from one of polyvinyl alcohol, nitrile rubber powder, polyacrylate, epoxy resin modifier or silicone rubber; the binder is optionally selected from one of waterborne polyurethane, sodium silicate solution, epoxy resin, polyvinyl formal or acrylic emulsion; the thickener is optionally selected from one of hydroxypropyl methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, xanthan gum or bentonite.
4. A method for preparing an environmentally friendly sheet material with self-purification capability, characterized in that: The preparation method is prepared by using the component materials contained in the environmentally friendly board with self-purification ability as described in any one of claims 1 to 3, comprising the following steps: Synthesis of MOFs; Preparation and compounding of nitrogen-doped carbon-based photocatalysts; Composite of graphene oxide; the introduction of antimicrobial agents and humidity regulating materials; The ultraviolet light absorber is added into the mixture and stirred; Introduction of toughening agents and self-healing polymers; Addition and molding of binders and thickeners.
5. The method for preparing an environmentally friendly plate with self-purification capability according to claim 4, characterized in that: The synthesis steps of the MOFs specifically include the following steps: The metal precursor and the organic ligand were mixed in a molar ratio of 1:1; Dissolving the mixture in N,N-dimethylformamide solvent with a solvent concentration of 0.1-0.2 mol / L; Solvothermal reaction is carried out at a temperature of 120-150°C and the reaction time is 12-24h; After the reaction was completed, the product was washed three times with ethanol; The washed product was placed in a vacuum oven at 80-100°C and dried for 8-12 hours.
6. The method for preparing an environmentally friendly plate with self-purification capability according to claim 4, characterized in that: The preparation and compounding steps of the nitrogen-doped carbon-based photocatalyst specifically include the following steps: Urea or melamine is placed in a closed crucible as a nitrogen source and calcined at 500-600° C. for 2-4 hours to prepare nitrogen-doped carbonized graphite; Mix tetrabutyl titanate, ethanol and urea, and adjust the pH of the solution to 3-4; Stir at 50-60°C for 4-6 hours to form a gel; The gel was dried in an environment of 70-80°C for 10-12 hours, and then calcined at 400-500°C for 2-3 hours to obtain nitrogen-doped TiO2 nanoparticles; MOFs and nitrogen-doped photocatalysts were mixed in a mass ratio of 2:1, dispersed in ethanol and subjected to ultrasonic treatment for 30-60 min; The mixture was stirred at room temperature for 6-12 h and then dried at 70-80 °C to remove the solvent.
7. The method for preparing an environmentally friendly plate with self-purification capability according to claim 4, characterized in that: The composite step of the graphene oxide is specifically The following steps are involved: Dispersing graphene oxide in deionized water at a concentration of 0.05-0.1 mg / mL, and performing ultrasonic dispersion for 25-30 min; Slowly add the MOFs-photocatalyst composite powder into the graphene oxide suspension and stir for 3-4 hours; The mixture is dried at 70-80°C to form a stable composite powder.
8. The method for preparing an environmentally friendly plate with self-purification capability according to claim 4, characterized in that: In the step of introducing the antibacterial agent and the humidity regulating material, the antibacterial agent and the humidity regulating material are weighed according to weight percentage and added to the composite powder, and stirred for 2-3 hours.
9. The method for preparing an environmentally friendly plate with self-purification capability according to claim 4, characterized in that: The step of introducing the toughening agent and the self-healing polymer specifically comprises the following steps: The toughening agent is made into a solution with a concentration of 5-10wt%; Slowly add the composite powder into the toughening agent solution and stir for 3-6 hours; Dissolving the self-healing polymer in a suitable solvent at a concentration of 10-20wt%; The toughened composite material is added into the self-healing polymer solution and stirred until uniform.
10. The method for preparing an environmentally friendly plate with self-purification capability according to claim 4, characterized in that: The steps of adding and molding the binder and thickener specifically include the following steps: The binder and the thickener are weighed and added to the composite material according to weight percentage respectively, and the mixture is fully stirred; Use molding or spraying process to evenly apply the mixed material on the surface of the building substrate; The coated material is placed under ultraviolet light or in an environment of 80-100°C for curing for 2-4 hours to complete the cross-linking and curing of the material.
Citation Information
Cited By
Heavy metal wastewater treatment agent and preparation method thereof
CN120348997A
Wood composite carbon-based environment-friendly odorless plate and preparation method thereof
CN121492186A